KAJIAN TENTANG EFEKTIVITAS PESAN DALAM KOMUNIKASI - Zikri Fachrul Nurhadi; Achmad Wildan Kurniawan (Universitas Garut, 2017)
Abstract. Message is one of the most important factors in communication. Therefore, there are some requirements in the effective communication so the message can result in feedback from communicant, namely: 1) The message which would be delivered has to be developed systematically, 2) Message delivered by communicator should be able to attract communicant, and 3) Message must be easily understood by communicant. Keyword: Efektivitas; Pesan; Komunikasi